Unveiling the drivers of vancomycin-resistant enterococcus in China: A comprehensive ecological study - Jiongjiong Wang; Xiaoying Li; Xinying Du; Huiqun Jia; Hui Chen; Jian Wu; Guangcai Duan; Haiyan Yang; Ligui Wang (Infectious Medicine)
Background: Vancomycin resistant enterococci (VRE) are now considered a global public health issue. In this study, we explored the relationship between vancomycin resistance incidence and various demographic and climatic factors. Methods: This retrospective study was performed between January 1st, 2014 and December 31st, 2021. Data covering the consumption of vancomycin, the prevalence of vancomycin resistance, and relevant demographics were collected. Spearman's rank correlation, beta regression, and spatial statistical analysis were performed using R version 4.2.2 and ArcGIS version 10.7. Results: Spearman's rank correlation described the positive relation between vancomycin consumption and the prevalence of vancomycin resistant Enterococcus faecium (VREfm). Multiple regression analysis showed that vancomycin consumption, rural population, proportion of population aged ≥65, annual temperature, and bed number in medical institutions per thousand people were significantly correlated with VREfm prevalence (r = 56.22, p < 0.001; r = 0.0002, p < 0.001; r = 0.06, p < 0.001; r = −0.07, p < 0.001; and r = −0.37, p < 0.001, respectively). Conclusions: Vancomycin utilization was the predominant factor contributing to VREfm resistance; the effects of rural populations and the proportion of the population aged ≥ 65 were significant but relatively minimal. Annual temperature and the number of beds in medical institutions per thousand people were protective factors against VREfm.